Landslide detection using ALOS optical and radar data. A case study from the Ilia prefecture. - Nikolakopoulos, K. G.; Choussiafis, Ch.; Karathanassi, V. (Bulletin of the Geological Society of Greece, 2013)
In this study the usefulness of the ALOS optical and radar data for landslide monitoring is examined. ALOS contains three sensors, commonly referred to as the “three eyes” of ALOS. These sensors are: the Panchromatic Remote-Sensing Instrument for Stereo Mapping (PRISM), the Advanced Visible and Near Infrared Radiometer type 2 (AVNIR-2), and the Phased Array type L-band Synthetic Aperture Radar (PALSAR). The area of study is located in a small village named Sykies near to the city of Andritsena in Western Peloponnese. The area suffered during the last years from enormous fires. As a result many landslides have been recorded. One of the latest Landslides has been recorded on January 2009 as a consequence of heavy rains. That landslide was mapped in situ using differential GPS. The possibility of detecting and mapping the specific landslide using ALOS data is examined in this study and the results are presented. Thirty ALOS radar images within a period of three years, two ALOS Prism data sets and two ALOS AVNIR collected over the same area within a year were used.